The Relationship between Synchronous Online Training Preference and Online Student Engagements - Saida Ulfa; Rex Bringula (Graduate School of Universitas Negeri Malang, 2022)
Online training during the pandemic was commonly held using the synchronous learning method. The aim of this study was to explore the relationship between synchronous online training preference, gender difference, and online student engagements (OSE). This study was analyzed with Structural Equation Model (SEM) by using SmartPLS 3 software. The participants of this study involved 35 online training participants and produced the following findings: 1) synchronous online training preference has a positive relationship with OSE variables, 2) The relationship between OSE variables is positive, 3) a gender has a positive relationship with skills, participation, and performance, while gender has a negative relationship with emotions and synchronous online training preference.